Solo Exhibition-: Stories of Dystopia, Chinese European Art Centre - Antoniou, Klitsa (My University, 2026)
Solo Exhibition-: Stories of Dystopia, Chinese European Art Centre, Xiamen, China Curated by Ineke Gudmansson